La región más transparente: las voces de la ciudad de México - María Fernanda Domínguez Reyes (Revista de Filología Románica, 2011)
Carlos Fuentes criticizes all optimistic vision about the development of the Federal District in his book The most transparent region. The pre-Columbian past and a present situated around 40´s and 50´s merge through some characters loaded of symbolisms. Fuentes shows how the city has lost all the splendor of what was Gran Tenochtitlan and has become a city of sin and lethargy. He demonstrates by putting on paper the contrasts between his characters lifestyles, conditioned by the environment where they live and the streets they pass through. This article is a little radiography of Mexico City.